Interdisciplinary Thematic Learning in Physical Education and Health under the New Curriculum Standards - Hu Nvying (International Journal of Education and Humanities, 2024)
This study investigates the feasibility and necessity of incorporating interdisciplinary thematic learning into physical education and health courses under the new curriculum standards. Addressing the current challenges in teaching methods, which often fail to effectively enhance students' comprehensive quality and knowledge integration, the research employs a literature review and case analysis. The findings highlight the crucial role of interdisciplinary learning in stimulating students' interest and improving their innovation and practical abilities. By promoting a more holistic educational approach, this method positively impacts students' lifelong sports awareness and healthy lifestyle habits. The study presents specific teaching strategies and recommendations to overcome existing problems in physical education and health instruction. These strategies include integrating various disciplines to create a more engaging and relevant learning experience, fostering an environment that encourages critical thinking and problem-solving skills, and implementing assessment methods that reflect students' overall development. Moreover, the research outlines a practical implementation path for interdisciplinary thematic learning, aligned with the new curriculum standards, to provide both theoretical and practical guidance for educators. This approach aims to bridge the gap between different subject areas, creating a more cohesive and comprehensive educational experience that prepares students for future challenges. By focusing on the benefits and practicalities of this method, the study seeks to offer valuable insights and tools for educators to enhance their teaching practices and ultimately contribute to the development of well-rounded, knowledgeable, and health-conscious students. This research underscores the potential of interdisciplinary thematic learning to transform physical education and health courses, making them more effective and relevant in today's educational landscape